Näsbyholm - parken och de närmaste omgivningarna ur ett historiskt och nutida perspektiv - Sunnerdahl, Klara; Gustavsson, Kristina; Åkerlund, Linda; Simonis, Robert; Blücher, Mia (2011)
The goal of this work has been to search historical materials, to identify the park's historical development, to prepare proposals on measures and that work should be the basis for further research. The aim has been to train us in searching for and use of materials and to gain an understanding of the process of work with older plants. In the process we have sought and found materials in archives, through literary and oral sources, and email contacts.